Fatores de risco para o óbito em hospitais gerais da rede FHEMIG - Lucimar Leao Gomes (2018)
Objective: To develop a predictive model for the death of hospitalized patients in general hospitals of the Hospital Foundation of the Minas Gerais State - Health Unified System (Fundação Hospitalar do Estado de Minas Gerais / FHEMIG - Sistema Único de Saúde / SUS), identifying the risk factors for death, through the profile of patients and hospitalizations for clinical and surgical diagnoses. Methods: The population that will be the source of this study constitute in patients and among those who died at the Medical and Clinical Surgery Clinics notified in the Integrated Hospital Management System (Sistema Integrado de Gestão Hospitalar - SIGH) of the general hospitals of the FHEMIG network, from January 01, 2016 to December 31, 2016. It is a quantitative, observational, comparative, retrospective search, that made effective through secondary data search. A descriptive analysis of the study variables was performed; bivariate analyzes between the outcome (death) and the predictive variables of interest; multivariate analysis, with death as a response variable, as predictors all those presenting values of p <0,15 in the bivariate analyzes and of the hospitalizations for clinical and surgical diagnoses classified with the twenty codes of Groups Related to Diagnosis - DRG, more frequent. Results: In hospitalizations for clinical diagnoses, the main independent risk factors for death were HIV-related diagnostic groups; the passage through U.T.I .; the hospital unit "H5"; the time of hospital stay between 0 - 3 days; evolution to surgery; the male sex and the age factor. For surgical diagnoses, the main independent risk factors for death were the passage through U.T.I .; the hospital unit "H5"; the age and the surgical characteristics: the non-use of prosthesis; the potential of infected surgical contamination. Conclusions: Identifying the risk factors for the death of hospitalized patients due to clinical and surgical diagnoses becomes important, since it can result in indicators to guide actions in favor of health processes with efficiency, quality and safety. The hospital information system used by the units of the FHEMIG network allows not only the automation of records and the integration of clinical and administrative information, which will guide health processes at certain times, but also favors analytical activity - as in the case risk factors for death. In order to do so, it is essential to promote adequate registration practices in the system.